Development and Study of Bacteriophage-containing Dosage Form for the Treatment of the Outer Ear Infections - E. O. Bakhrushina; M. N. Anurova; S. S. Bochkareva; A. M. Vorobev; Yu. O. Shcherbina; M. A. Pasivkina; L. O. Krekhtunova; N. B. Demina; A. V. Aleshkin (Разработка и регистрация лекарственных средств)
Introduction. Infectious otitis externa and middle ear can cause hearing loss, which significantly reduces the quality of life of patients. The main causative agents of acute bacterial otitis media are Pseudomonas aeruginosa and Staphylococcus aureus. This article is devoted to the development and study of a novel dosage form for treatment of infectious diseases of the external ear containing bacteriophages that lyse bacterial strains of Pseudomonas aeruginosa. Ear drops were considered as a promising dosage form for instillation into the ear canal.Aim. The aim of the work is to develop a dosage form of Pseudomonas aeruginosa bacteriophages for the local treatment of infectious otitis media.Materials and Methods. The active substances of the developed drug are bacteriophages that lyse bacterial strains of Pseudomonas aeruginosa: PA5 and PA10, which were obtained by growing on a solid growth medium in mattress flasks with subsequent sterilizing filtration through a membrane filter (0,22 µm) and elimination of endotoxins on a chromatographic column. To obtain experimental compositions, excipients that do not cause a drop in the titer of bacteriophages were used – purified water as the solvent, viscosity modifiers: glycerol (CHIMMED, Russia) and a mix of macrogol 6 and glyceryl caprilocaprate brand Softigen 767 (Cremer, Germany), antioxidant Ethylenediaminetetraacetic acid (EDTA), preservatives nipagin and nipazole. The obtained samples were standardized according to pharmacopoeial indicators, recommended for the dosage form "drops" – density, pH, viscosity. For all experimental compositions, the stability of the titer of bacteriophages was studied by the Gratia method for 6 months. The local irritation and systemic effects were also studied on five chinchilla male rabbits.Results and discussion. As a result of the conducted research, four experimental compositions of ear drops with a cocktail of bacteriophages PA5 and PA10 were obtained. The optimal technological characteristics were observed in the composition containing glycerol as a viscosity modifier at a concentration of 10,0 %. For optimal composition, the stability of the bacteriophages cocktail titer, local irritating and systemic effects were analyzed. The study revealed stability of the bacteriophages PA5 and PA10 titers in the composition of dosage form, and absence of local irritating and systemic effects of ear drops.Conclusion. The dosage form can be recommended for preclinical studies.